A novel healthy blood pressure phenotype in the Long Life Family Study. Issue 1 (January 2018) - Marron, Megan M.; Singh, Jatinder; Boudreau, Robert M.; Christensen, Kaare; Cosentino, Stephanie; Feitosa, Mary F.; Minster, Ryan L.; Perls, Thomas; Schupf, Nicole; Sebastiani, Paola; Ukraintseva, Svetlana; Wojczynski, Mary K.; et al.
Abstract : Background: Hypertension tends to run in families and has both genetic and environmental determinants. We assessed the hypothesis that a novel healthy blood pressure (BP) phenotype is also familial and sought to identify its associated factors. Methods: We developed a healthy BP phenotype in the Long Life Family Study, a cohort of two-generation families selected for longevity. Participants from the offspring generation ( n = 2211, ages 32–88) were classified as having healthy BP if their age-adjusted and sex-adjusted SBP z -score was between −1.5 and −0.5. Offspring on antihypertensive medications were classified as not having healthy BP. Families with at least two offspring ( n = 419 families) were defined as meeting the healthy BP phenotype if at least two and at least 50% of their offspring had healthy BP. Results: Among 2211 offspring, 476 (21.5%) met the healthy BP phenotype. When examining the 419 families, only 44 (10.5%) families met the criteria for the healthy BP phenotype. Both offspring and probands from families with healthy BP performed better on neuropsychological tests that place demands on complex attention and executive function when compared with offspring and probands from remaining families. Among families with the healthy BP phenotype compared with families without, a higher proportion of offspring met the American Heart Association definition of ideal cardiovascular health (10.8 versus 3.8%, respectively; driven by BP, smoking status, and BMI components). Conclusion: In this cohort of familial longevity, few families had a novel healthy BP phenotype in multiple members. Families with this healthy BP phenotype may represent a specific pathway to familial longevity. Abstract : Supplemental Digital Content is available in the text